Student perceptions of a trial Religious Education curriculum: establishing baseline data - Sultmann, William (Journal of beliefs and values, 2021)
Australian students’ perception of a trial Religious Education (RE) programme is the focus of this paper. Students (N = 1478) from 37 schools, primary and secondary, completed an online survey that included six Likert style items that aligned with six RE development principles that guided the development of the trial. Curriculum development was inclusive and student centred, giving voice to student input. Results indicate that the students generally held high perceptions of the trial RE curriculum with the highest ratings for principles being Jesus as Model and Message, Experiential Learning through Inquiry and Deep Learning. Female students, those in the earlier years of schooling, and students from smaller schools most valued the trial curriculum as indexed by measures of its development principles. Implications from student evaluations demonstrated an overall high level of satisfaction with learning engagement while highlighting the complexity of language and developmental differences for interpreting student learning in Religious Education.